2016
DOI: 10.1093/mnras/stw548
|View full text |Cite
|
Sign up to set email alerts
|

Levitating atmospheres of Eddington-luminosity neutron stars

Abstract: We construct models of static, spherically symmetric shells supported by the radiation flux of a luminous neutron star in the Schwarzschild metric. The atmospheres are disconnected from the star and levitate above its surface. Gas pressure and density inversion appear in the inner region of these atmospheres, which is a purely relativistic phenomenon. We account for the scattering opacity dependence on temperature green by using the Klein-Nishina formula. The relativistic M 1 closure scheme for the radiation t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Wielgus et al (2015) have shown that it is possible to create an optically thin atmosphere at this radius which levitates above the surface of the star, supported entirely by radiation. Wielgus et al (2016) have extended the analysis to include optically thick atmospheres as well.…”
Section: Introductionmentioning
confidence: 99%
“…Wielgus et al (2015) have shown that it is possible to create an optically thin atmosphere at this radius which levitates above the surface of the star, supported entirely by radiation. Wielgus et al (2016) have extended the analysis to include optically thick atmospheres as well.…”
Section: Introductionmentioning
confidence: 99%
“…The rotation period of the center of the torus is 68 M, and the simulation is carried out until t = 100 M, thus spanning nearly one and a half orbital periods. Although this kind of solutions are known to be unstable to the MRI and the Papaloizou-Pringle instability in 3D (Wielgus et al 2015;Bugli et al 2018), the time elapsed by our simulations still corresponds to the initial phase of the linear growth, and no chaotic behaviour can be observed. In fact, the torus here presented is identical to Case A simulated by Wielgus et al (2015), who reported perturbations at t = 100 M still at the ∼ 10 −4 level.…”
Section: Stationary Torusmentioning
confidence: 70%
“…However, here we have only considered optically thin atmospheric shells, whereas the atmospheres of X-ray bursters are optically thick. For this reason we are postponing a detailed discussion of bursters to another paper, where optically thick solutions will be reported (Wielgus et al 2015). The atmospheres presented here can be thought of as an (extreme) example of density and pressure inversion.…”
Section: Discussionmentioning
confidence: 88%
“…This paper discusses the simplest case of optically thin, spherically symmetric atmospheres in the Schwarzschild metric, which admit of analytic solutions. Optically thick atmospheres require numerical treatment of radiative transfer, and these will be reported elsewhere (Wielgus et al 2015).…”
Section: Introductionmentioning
confidence: 99%